2018
DOI: 10.1080/1828051x.2018.1427006
|View full text |Cite
|
Sign up to set email alerts
|

Dorper × Santa Ines F1 crossbred lambs under different grazing times and supplement levels in tropical regions: performance and macromineral requirements

Abstract: The objective of this study was to evaluate the performance and net requirements for calcium (Ca), phosphorus (P), magnesium (Mg), potassium (K) and sodium (Na) in Dorper  Santa Ines F1 crossbred lambs under different grazing times and supplement levels. We used 36 uncastrated male lambs with initial body weights (BW) of 15.5 ± 1.9 kg. Twelve animals were used as a reference group, and the remaining 24 animals were divided into three treatments according to grazing time and supplement level: 9 h  1.2% BW, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
4
2
0
Order By: Relevance
“…The value advocated by this committee is not in accordance with the needs of animals raised in tropical conditions, and enhanced levels of recycling of these nutrients may occur in animals raised under these conditions. This observation has also been reported by Assis et al (2018). Trace mineral requirements vary during stages of growth due to changes in the metabolic needs of individual tissues (Masters et al, 1999).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The value advocated by this committee is not in accordance with the needs of animals raised in tropical conditions, and enhanced levels of recycling of these nutrients may occur in animals raised under these conditions. This observation has also been reported by Assis et al (2018). Trace mineral requirements vary during stages of growth due to changes in the metabolic needs of individual tissues (Masters et al, 1999).…”
Section: Resultssupporting
confidence: 90%
“…Results obtained for Santa Inês and Morada Nova sheep revealed that both breeds contained lower percentages of Ca (7.33% and 11.7%, respectively) and greater percentages of P (13.6% and 7.28%, respectively) than values reported by AFRC (1991) and ARC (1980) and that Ca and P percentages were similar to those observed by Assis et al (2018), who also worked with Santa Inês sheep, which were allowed to graze on vegetation of the Caatinga Biome. The ARC (1980) committee recommended that 1.5 g/d Ca and 0.7 g/d of P be provided per 100 g BW gain.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations